Challenging urban health: towards an improved local government response to migration, informal settlements, and HIV in Johannesburg, South Africa - Joanna Vearey (Taylor & Francis Group, 2011)
This article is a review of the PhD thesis undertaken by Joanna Vearey that explores local government responses to the urban health challenges of migration, informal settlements, and HIV in Johannesburg, South Africa. Urbanisation in South Africa is a result of natural urban growth and (to a lesser extent) in-migration from within the country and across borders. This has led to the development of informal settlements within and on the periphery of urban areas. The highest HIV prevalence nationally is found within urban informal settlements. South African local government has a 'developmental mandate' that calls for government to work with citizens to develop sustainable interventions to address their social, economic, and material needs. Through a mixed-methods approach, four studies were undertaken within inner-city Johannesburg and a peripheral urban informal settlement. Two cross-sectional surveys - one at a household level and one with migrant antiretroviral clients - were supplemented with semi-structured interviews with multiple stakeholders involved with urban health and HIV in Johannesburg, and participatory photography and film projects undertaken with urban migrant communities. The findings show that local government requires support in developing and implementing appropriate intersectoral responses to address urban health. Existing urban health frameworks do not deal adequately with the complex health and development challenges identified; it is essential that urban public health practitioners and other development professionals in South Africa engage with the complexities of the urban environment. A revised, participatory approach to urban health - 'concept mapping' - is suggested which requires a recommitment to intersectoral action, 'healthy urban governance' and public health advocacy.